REDESCRIPTION OF TWO SPECIES OF GENUS EUPEODES OTEN SACKEN FROM QUETTA BALOCHISTAN, PAKISTAN - J. K. Turk; N. Memon; B. Mal; S. A. Memon; M. A. Shah; D. A. Solangi (Journal of Animal and Plant Sciences, 2015)
Eupeodes corollae Fabricius and Eupeodes latifasciatus Macquart are the members of aphidophagus genus Eupeodes Osten Sacken belongs to order Diptera. These species of hoverflies economically very important, adults are very good pollinators and their larvae are predators, which feed on the aphids, which cause serious damage to our cash crops and vegetables. In present study, two species of hoverflies are recorded from Quetta Balochistan, Pakistan. These species are redescribed on the basis of the morphological characters, male and female external and internal genitalia.
Keywords: Eupeodes corollae; Eupeodes latiasciatus; Quetta; Balochistan; Pakistan